Libérer l'espace liturgique: Liberating Liturgical Space - Duthilleul, Jean-Marie (Studia liturgica, 2026)
The space given by God to man is the instrument that connects man with things, with others, and with God. It constantly fulfils what it signifies, as at World Youth Day in Paris in 1997, when the young people gathered around the Pope visibly formed the Body of Christ. The liturgical space must also be designed to signify the liturgy that takes place there: to enter into relationship with other faithful, with God, and to make Christ present among us. For this, we need to return to the origins of church buildings and create, for each place and with each community, the liturgical space that will allow it to best bear witness to its life and faith, within the liturgy that gathers it, far from any predefined scheme.